Periscope of Ideas Selective Criteria for the Application of Restorative Justice in Corruption Crimes - Wangga, Maria Silvya E.; Ahmad, Nadzriah; Puluhulawa, Jufryanto; Swarianata, Vifi (Universitas Negeri Semarang, 2024)
This article applies the theory of restorative justice to the analysis of state losses resulting from corrupt activities. This study employs socio-legal research, which is a type of normative legal research that is dependent on values and facts. The study's findings revealed that two (2) points of view are based on the fundamental notion that restorative justice can compensate the state for damages incurred through acts of corruption. First, in order to make up for the losses sustained by the state as a result of corrupt criminal acts, law enforcement must be centered around the idea of restorative justice. Secondly, the fact that the Constitutional Court's ruling Number 25-PUU-XIV-2016 eliminated the word